2019
DOI: 10.3390/ijerph16234734
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Temporal and Geographic Patterns of Myocardial Infarction Hospitalization Risks in Florida

Abstract: Knowledge of geographical disparities in myocardial infarction (MI) is critical for guiding health planning and resource allocation. The objectives of this study were to identify geographic disparities in MI hospitalization risks in Florida and assess temporal changes in these disparities between 2005 and 2014. This study used retrospective data on MI hospitalizations that occurred among Florida residents between 2005 and 2014. We identified spatial clusters of hospitalization risks using Kulldorff’s circular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…It is also possible that geographic differences in comorbidities may play a role in the observed DRMR clustering. Previous research indicated that the northern parts of Florida exhibit significantly higher rates of comorbidities, including hypertension, heart disease, and kidney disease, compared to other regions within the state ( Smith et al, 2018 ; Odoi et al, 2019 ). Comorbidities in individuals with diabetes can further increase the risk of mortality through their adverse effects on blood pressure, myocardial infarction, cancer risks, kidney function, and blood sugar control.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that geographic differences in comorbidities may play a role in the observed DRMR clustering. Previous research indicated that the northern parts of Florida exhibit significantly higher rates of comorbidities, including hypertension, heart disease, and kidney disease, compared to other regions within the state ( Smith et al, 2018 ; Odoi et al, 2019 ). Comorbidities in individuals with diabetes can further increase the risk of mortality through their adverse effects on blood pressure, myocardial infarction, cancer risks, kidney function, and blood sugar control.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of high-risk clusters in Calhoun, Gadsden, and Jackson counties in Northwest Florida both when hospitalized cases were -divided by the total number of cases and by the county population suggests that despite the lower COVID-19 incidence risks in Northwest Florida compared to Southern Florida, a large proportion of the cases in Northwest Florida were severe enough to warrant hospitalization. Northwest Florida is a predominantly rural region with large proportions of black and older residents, and high burdens of comorbidities such as diabetes, hypertension and cardiovascular disease [ 81 , 100 102 ]. Moreover, similar to what was reported for black patients in California [ 103 ], limited access to outpatient testing sites in Northwest Florida [ 37 ] may result in a large proportion of black segments of the population accessing testing in hospitals when symptoms are already severe.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that despite reduced opportunities for the SARS-COV-2 virus to spread in the sparsely populated rural Florida counties, these locales have, on average, larger proportions of older (> 65 years) residents and higher burdens of underlying chronic health conditions such as obesity [ 117 ] diabetes [ 81 , 101 ], hypertension [ 100 ], and heart disease [ 102 , 118 , 119 ] compared to urban counties. Rural areas also tend to have low health insurance rates and a less robust healthcare infrastructure [ 120 – 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth pointing out that other studies have used FSSS to identify spatial clusters of other health outcomes such as measles ( Tang et al, 2017 ), cancer ( Katayama et al, 2014 ; Amin, Nelson & McDougall, 2018 ), suicide mortality ( Yamaoka et al, 2020 ), and cardiovascular diseases ( Roberson et al, 2019 ; Odoi et al, 2019 ). Recent research in Florida has demonstrated that FSSS is a useful technique for the identification of geographic disparities in stroke prevalence ( Roberson et al, 2019 ) and hospitalizations due to myocardial infarction ( Odoi et al, 2019 ). Suffice it to say that populations living within the identified pre-diabetes clusters identified in the current study have disproportionately high risks of the condition and, therefore, control efforts should focus on these areas in order to reduce the observed disparities.…”
Section: Discussionmentioning
confidence: 99%